Indonesia matters Asia's emerging democratic power - Acharya, Amitav (World Scientific, 2015)
"[This book] analyses Indonesia's foreign policy and international role under the democratic regime, with particular focus on its role as a leader of ASEAN, its relationship with the major powers of the Asia Pacific, and its place in global order of the 21st century"